Nutritional Quality of Commercially Important Marine Fishes Scomberomorus Guttatus And Cynoglossus Semifasciatus - G.Chitra; B.Dhanalakshmi (International Journal of Pharma and Bio Sciences, 2020)
The marine fish are extraordinarily nourishing food and are an affluent fish meat source. The measurement of some proximate profiles such as protein, lipids, moisture and pH contents in fresh and dried fishes are often necessary to ensure that they meet the requirements of food regulations in nutrition aspects and commercial specifications. The objective of this work was to analyze the proximate composition of fresh and dried fishes of Scomberomorus guttatus and Cynoglossus semifasciatus. Higher pH and moisture content was recorded in fresh Scomberomorusguttatus (7.1±0.02 and 70.02±0.10%) than the dried samples (6.4±0.13 and 0.61±1.00%). Similarly fresh samples of Cynoglossus semifasciatus had higher pH and moisture content (6.9± 0.11 and 69.54± 0.06%) than the dried samples (6.5±0.09 and 0.57±0.10%). Fresh samples of Scomberomorusguttatus and Cynoglossus semifasciatus had higher protein content (4.4±.010mg/100g and 2.6±0.03mg/100gm) compared to the Likewise highest lipid content was found in fresh Scomberomorus guttatus (1.64±0.08gm) and Cynoglossus semifasciatus (1.3±0.04gm) than the dried samples. Proximate biochemical composition of all species showed that their percentage of protein and fat content are good and can be a food item in parallel to the bony fishes.